Keabsahan Kepemilikan Hak Cipta Koreografi di Lingkungan Dosen Institut Seni Indonesia Yogyakarta - Khotimah, Viviyani (JIPRO: Journal of Intellectual Property, 2018)
Ownership of choreographic copyright has been regulated in Article 40 of Law Number 28 of 2014 concerning Copyright. The effect of ownership of this Copyright is the same as the ownership of other works, which is the same as having exclusive rights in the form of moral rights and economic rights. Dance Department Lecturer at the Yogyakarta Indonesian Institute of Arts is an active party in the creation of choreography, but the ownership of the copyright is specifically regulated in Article 35 because of its status as a Civil Servant, where the creation of choreography done in official relations is considered as the creator is Government Institution except before there is an agreement related to copyright ownership. This provision has created its own problems in practice. This is what happened to the Dance Department Lecturer at the Indonesian Art Institute in Yogyakarta, because the choreography works created by the Lecturers was recognized as their copyright. In this context, it has the potential to cause copyright infringement as stipulated in Article 35 of Law No. 28 of 2014 about Copyright